Gen Y’s Preferences for Learning in Malaysia - Abu Bakar, Zuraida; Mashahadi, Faizah (Advances in Social Sciences Research Journal, 2024)
Gen Y born between 1980 until 2000, currently the most important generation in Malaysia's workforce. They stand out from the crowd that they value open communication, look for a positive work environment, and give work-life balance a higher priority. They probably operate well in teams and in groups. Thus, some learning preferences will improve Gen Y's productivity at the workplace. Gen Y employees will continuously deliver excellent work if they are able to develop personally via their work experiences. There is an efficacy level to some learning preferences that may be measured. This study will objectively assess a few helpful learning preferences in order to assist everyone in the workplace in understanding the phenomenon of Gen Y and their learning preferences in Malaysia. The purpose of this article is to help Gen Y employees apply their newfound knowledge to enhance their performance at work. There are three learning preferences such as informal learning, flexible learning, and mentoring that will enhance Generation Y's performance are presented in this study. Since the learning preferences will be the financial investment that drives Gen Y to become extremely effective employees in Malaysia, they are vital for any organization.